The Role and Significance of the Compliance Control System in the Prevention of Corruption Risks in the Public and Private Sectors - Sultonov Mukhammad Shokh Abdurashid ugli (Genius Publishing Group, 2022)
This article discusses the role and importance of compliance control systems in preventing corruption risks in the public and private sectors. That the negative consequences of corruption are much more serious and larger than the positive ones. In the private sector, it may be more difficult for a multinational company to identify key bribery risks, especially if it operates in multiple jurisdictions and has multiple agents or intermediaries. Such companies often have high corruption risks as well as reputational risks. Keep in mind that it is easier to bribe a small intermediary organization than a large multinational company.
Keywords: Corruption; Public; Private Sector; Risk Of Corruption